PENGEMBANGAN KESEHATAN MELALUI PEMANFAATAN OLAHAN TANAMAN TOGA MENJADI TEH HERBAL PENURUN TEKANAN DARAH - E. Amigo, Thomas Aquino; Erwanto, Rizky; Muflih, Muflih (Universitas Respati Yogyakarta, 2021)
Utilization of medicinal plants into processed drinks, is still very rarely done. In fact, this activity can suppress the use of chemical drugs in the treatment of hypertension. Therefore, it is necessary to carry out community service activities that can foster interest in the management of medicinal plants into herbal teas. The results of this community service activity found that some community representatives were able to mention the meaning of hypertension, avoiding hypertension risk factors which were marked by more than 60% of the residents who attended mentioning hypertension prevention, almost 80% could mention hypertension prevention. The public knows the risk factors that can cause hypertension and from the people who attended said they would take better care of their health by using herbal plants.Keyword: Hypertension; Medicinal Plants, Herbal Tea